Mathematical modeling of chemisorption process at chlororganic productions - Безносик, Юрий Александрович (Technology audit and production reserves, 2014)
The data on mathematical modeling of simultaneous chlorine and hydrogen chloride absorption by alkaline solutions are given in the paper. The purpose of the paper is to analyze the sanitary column operation and develop the mathematical model of exhaust gas purification from chlorine and hydrogen chloride. The exhaust gas neutralization process proceeds in countercurrent absorption columns, which are irrigated by the alkaline solution. Mathematical model of the process includes a system of differential equations of component-wise material balance. The material balance equation system describes the change in the component concentration according to the column height. The equation system is written taking into account the assumptions that the process is isothermal, proceeds in the full displacement in both phases; only hydrogen chloride and chlorine are absorbed from the gas flow and chemisorption reaction in the liquid phase runs immediately. The reaction surface in this case coincides with the interface, the reaction proceeds in the external diffusion region. The process rate is determined only by the diffusion rate of the components from the gas flow to the reaction surface. The actual kinetics is not taken into account. The equations of the mathematical model allow to calculate the concentration profiles of the components according to the column height. Using the mathematical model of chemisorption of two gases allows to make calculations of similar columns at the design stage and the stage of production process investigation.